Kualitas Fisika-Kimia Air di Areal Budidaya Desa Kaima, Eris dan Toulimembet, Kabupaten Minahasa, Provinsi Sulawesi Utara - DeBreving, Zainal M.; Rompas, Robert J. (e-Journal BUDIDAYA PERAIRAN, 2013)
ABSTRACT Water physical-chemical quality at fish farming area in Kaima, Eris and Toulimembet villages around Lake Tondano was observed. Water quality parameters including temperature, pH, brightness and dissolved oxygen were measured in situ. Observation was conducted at three stations, which were waters around Kaima, Eris, and Toulimembet villages. Measurement was carried out at 2-points at each station, where appointing of both points was based on the consideration of the activities of fish farming and settlement layout. Point-1 represented the activities of fish farming whereas point-2 represented the settlement activity. Data were collected at one week interval. Results showed that water temperature ranged from 26 - 27 0C; brightness was above 2 m; dissolved oxygen ranged from 2.5 - 8.3 ppm and pH ranged from 7,9 - 8,7. Based on the water quality criteria for aquaculture, water quality parameters on fish farming area in Kaima, Eris and Toulimembet, were still suitable for fish farming activities. Keywords: Lake Tondano, water quality, fish farming